Using Substances to Enhance Performance: A Psychology of Neuroenhancement - Ralf Brand (Frontiers Research Topics, 2017)
Neuroenhancement (NE) is a behavior conceptualized as the use of a potentially psychoactive substance to enhance ones' already proficient cognitive capacities. Depending on the specific definitions used, prevalence estimates vary greatly between very low 0.3% (for illicit substances) to astonishingly high 89% (for freely available lifestyle substances). These variations indicate that further research and more conceptual and theoretical clarification of the NE construct is dearly needed. The contributions of this research topic aim to do just that. Specific questions addressed are: How prevalent is NE behavior? How can NE research profit from the already more evolved field of social science research on doping in sports? How is NE perceived by the public? What psychological processes and variables play a role in the decision to neuroenhance? A wide array of methodological approaches is used to investigate these questions. The topics contributions range from theoretical to experimental accounts on NE, and they utilize a diverse set of methods ranging from qualitative to neuroscientific approaches. The research presented here represents a first step towards what we have labeled a psychological approach to NE. By addressing the questions above this research topic hopefully advances our understanding of NE behavior. As with every new field of research, new answers always prompt new questions. In light of what we know now about NE, we hope that the findings presented here will be pursued by other researchers in the future. Clearly, the endeavor to understand NE behavior has only just begun.